To study the cumulative properties of an immunostimulant based on 1,2,4-triazole - O.-L. I. Labunska; V. M. Hunchak; B. V. Gutyj; M. P. Soltys (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
During the study of the cumulative properties of the new immunostimulant “Immunokor,” it was found that its 28-day intramuscular (in increasing doses) administration to the tissues of laboratory animals (white rats) does not cause death. The cumulation coefficient of the studied agent is 12.9 units, which defines it as a drug that does not have cumulative properties. The observations confirmed that intoxication's occurrence and clinical manifestations were not observed. Against the background of slight depression, inactivity, and lack of appetite in individual animals of the experimental group, which occurred only in the first 10 days of the experiment, full compliance with behavioral and reflex reactions in animals was revealed. There were no disorders of the central nervous system, digestive, and excretory systems. The skin and the skin in the experimental group's animals did not differ in any way from their counterparts in the control. No local or reflex reaction to the drug or an allergic reaction to its repeated administration was detected. Intramuscular administration of the drug “Immunokor” did not affect the body weight of rats in the experimental group. The revealed tendency to change the weight coefficients of the liver, spleen, and kidneys is a short-term and restorative reaction of the organism of experimental animals to prolonged and significant doses of a foreign substance. When studying the cumulative properties of Immunokor, it was found that it can cause specific shifts in the homeostasis of experimental rats. In the absence of significant morphological changes from the hematopoietic system, signs characteristic of a negative assessment of the functional state of the liver were detected (increase in volume, change in color, pinpoint hemorrhages, increase in serum creatinine concentration, and AST activity). It was found that already 14 days after the last intramuscular injection of the drug, the studied indicators (weight coefficients of internal organs, hematological and biochemical blood parameters) characterized the absence of any macrostructural and functional changes in the body of laboratory animals.